A Qualitative Investigation of the role of Religious Educational Institutes in promoting tolerance versus extremism in Faisalabad Pakistan - Dr. Basharat Ali; Dr. Muhammad Shabbir Chaudhry; Farhan Amjad; Zeeshan Riasat; Muhammad Sharjeel Younas; Muhammad Asif; Muhammad Faisal Zahid; Hammad Hassan Zubair; Dr. Falak Sher (Corresponding Author) (Journal of Religion and Society, 2026)
Religious educational institutes have crucial impact on the societal attitudes towards tolerance and extremism in Pakistan. This research paper includes the qualitative investigation of religious educational institutes` role in promoting tolerance versus extremism in Pakistani society, as madrassas are one of the most important parts of Pakistani education system. This study aims to investigate the role of religious educational institutes typically called madrassas in promoting tolerance in society or they are promoting extremism in society. For qualitative investigation in-depth interviews were conducted and the respondents were teachers of religious institutes. This study was conducted in Faisalabad and teachers from four madrassas were selected as population. Purposive sampling from non-probability sampling was used. The results show that religious educational institutes in Faisalabad tend to promote tolerance in society as they discourage extremism through their teachings and they promote the counter extremist ideologies in society. Keywords: Religious Education, Religious Extremism, Qualitative Study, Madrassas